The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0104-12902013000300010
|View full text |Cite
|
Sign up to set email alerts
|

Inatividade nos deslocamentos para o trabalho e fatores associados em industriários

Abstract: Este trabalho foi realizado com o apoio logístico do Serviço Social da Indústria de Pernambuco (SESI/PE).Inactive commuting to work and associated factors in industrial workers 1 Inatividade nos deslocamentos para o trabalho e fatores associados em industriários 63 AbstractThis study analyzed the prevalence and identified the factors associated with inactive commuting to work among industrial workers from Pernambuco, Brazil. Data for this cross-sectional study were gathered from a sample of 1,910 industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
2
0
4
Order By: Relevance
“…In this study, all of the data used were self-reported, whereas in some of the studies conducted in high-income countries (similar to the United States of America) only information directly measured in the population of interest was used 13 . Once self-reported measures tend to be less precise than those measured directly, the prevalence rates presented here tend to be less accurate than those in studies in which factors were directly investigated 14,15 . It is a known fact that, based on survey data similar to PNS, the adult population of the country tends to overestimate positive behaviors (such as the recommended consumption of fruits and vegetables) and to underestimate those with negative connotation (such as smoking) and biological markers (such as high total cholesterol, blood glucose and blood pressure), which compose the underdiagnosed conditions 16,17 , leading us to the conclusion that the ideal CVH of the Brazilian population is even worse than that described in our results.…”
Section: Discussionmentioning
confidence: 72%
“…In this study, all of the data used were self-reported, whereas in some of the studies conducted in high-income countries (similar to the United States of America) only information directly measured in the population of interest was used 13 . Once self-reported measures tend to be less precise than those measured directly, the prevalence rates presented here tend to be less accurate than those in studies in which factors were directly investigated 14,15 . It is a known fact that, based on survey data similar to PNS, the adult population of the country tends to overestimate positive behaviors (such as the recommended consumption of fruits and vegetables) and to underestimate those with negative connotation (such as smoking) and biological markers (such as high total cholesterol, blood glucose and blood pressure), which compose the underdiagnosed conditions 16,17 , leading us to the conclusion that the ideal CVH of the Brazilian population is even worse than that described in our results.…”
Section: Discussionmentioning
confidence: 72%
“…Alguns estudos apontam relação negativa da caminhada e do ciclismo como meio de transporte utilizado para ir ao trabalho. Hardman et al 15 17 . De modo adicional, a percepção da insegurança pública tem provocado alterações significativas na escolha dos modos de transporte, desfavorecendo os deslocamentos urbanos a pé ou de bicicleta 18;19 .…”
Section: Discussionunclassified
“…Another limitation refers to the fact that pre-employment medical tests are performed when workers enter the construction industry, selecting only the healthiest individuals to work in the companies. This selection may lead to the occurrence of a "healthy worker effect", whereby workers with established hearing loss are rejected after the medical tests 33,34 . Also, we should not exclude a possible memory bias because the questionnaire is based on participants' recall, in which the most exposed workers may have better remembered the activities with risks of hearing loss.…”
Section: Resultsmentioning
confidence: 99%